Penelitian Team Management Yang Baik dan Efisien Bagi Perusahaan Besar dan Organisasi dengan Multi Project - Michael Anggawinarta; Christian Anggrianto (Universitas Ciputra Surabaya, 2017)
In this research we discuss about how is it to resolve the problem in the complexcity in projects that keep evolving, and make us have to keep making a good strategy to make an optimal result. In this research, we discuss about how to make a good valuation matrix for the succes level in certain project. the criteria of a successsful project it self have a lot of point of view that could influence the result of the project. The ideal things in a project should have is objectives and the clear steps to get there. With the clear objectives and steps this project will bear the best result.. For reaching those results there’s also need some roles in the team so there’s someone will fasilitate the progress in the working of the project. The last thing that needed to be noted is the steps that needed to take to be a successful team is Plan, Do, Act, Check Cyle